Nursing Contributions to Reducing Clinical Information Loss During Shift Transitions - Alshammari, Abeer Raji S; Alshammari, Meshal Hadi A; Alruwaili, Saud Ghadhban H; Alanazi, Hamidah Tumaysh F; Mohammmed Ahmed S Almohammadi; Alanazi, Fehaid Dughām M; Alanazi, Ayed Dughām M; Maha Alhassan Mohammed Almalki; Hind Nafa Alfhege; Adwaa Ibrahim Abdullah Alghamdi; et al. (International Journal of Computational and Experimental Science and Engineering, 2024)
The modern healthcare environment is a complex, high-stakes ecosystem where the continuous, accurate, and timely flow of clinical information is the cornerstone of patient safety, care quality, and optimal outcomes. Within this dynamic setting, the points of transition—particularly the handoff of patient care responsibility from one nursing shift to another—represent critical junctures of vulnerability. These transitions are not mere procedural formalities but are, in essence, the transfer of the cognitive model of the patient: their history, current status, anticipated trajectory, and the nuanced plan of care. It is during these handoffs that the risk of clinical information loss, distortion, or omission is significantly heightened, with potentially severe consequences for patient well-being (1, 2).